Analisis Pola Asuh dan Komunikasi Orang Tua pada Remaja Geng Motor Kelurahan Jati Utomo Kota Binjai - Putri, Sabrina Dwi; Fidorova, Yolanda; Cantika, Cantika; Ariqi, Faiz Rhido; Rajab Harahap, Mhd Abdul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Juvenile delinquency occurs along with the development of technology, where their behavior is deviant and violates norms to the occurrence of crime. In this phase, a good role and communication between parents and children is needed because there are many emotional, cognitive and physical changes.This study aims to determine the form of parenting and communication of parents in teenage motorcycle gangs in Jati Utomo Village, North Binjai, North Sumatra and the method used in this study is descriptive qualitative. This research data collection technique uses interviews, observations and literature studies. The subjects of the study were several motorcycle gang members and several neighborhood heads in Jati Utomo Village. The results of this study show that the form of parenting greatly affects the way adolescents get along, as well as the communication built between parents and children which is a guide in determining their social environment. Teenagers make the community formed as a forum that can express themselves and get a very wide scope of friends. While the form of parenting they get from parents is very minimal, ranging from teaching responsibility, mentoring worship problems and solving social life problems they experience Keyword: Parenting, Teen, Motorcycle Gangs